Analisis Kemampuan Berpikir Kritis Siswa SMA Berkemampuan Matematika Tinggi dalam Menyelesaikan Masalah Fungsi - Siskatur Riskiyah; Ukhti Raudhatul Jannah; Septi Dariyatul Aini (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2018)
This study aims to describe the analysis of students' critical thinking abilities with high mathematics abilities in solving functional problems at SMAN 1 Pamekasan. This research was conducted at SMAN 1 Pamekasan with the research subjects of 3 students with high math abilities from 36 students of class X-F. This research is a case study with a qualitative approach. Data is collected through test methods, interviews, and documentation. The results of the study explain that in solving the function problems in the form of a story about the linear function of the three subjects able to fulfill all indicators of critical thinking, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. However, the three subjects have different critical thinking abilities when solving problems in the form of stories about quadratic function. The difference is the first subject meets all indicators of critical thinking, the second subject meets all critical thinking indicators except inference and self-regulation indicators, while the third subject only fulfills evaluation and explanation indicators. Information about the description of students' critical thinking abilities with high mathematics ability can be used as information to design the right learning process in the world of education.